2009
DOI: 10.1371/journal.pone.0004181
|View full text |Cite
|
Sign up to set email alerts
|

Serum Activity of Platelet-Activating Factor Acetylhydrolase Is a Potential Clinical Marker for Leptospirosis Pulmonary Hemorrhage

Abstract: Pulmonary hemorrhage has been recognized as a major, often lethal, manifestation of severe leptospirosis albeit the pathogenesis remains unclear. The Leptospira interrogans virulent serogroup Icterohaemorrhagiae serovar Lai encodes a protein (LA2144), which exhibited the platelet-activating factor acetylhydrolase (PAF-AH) activity in vitro similar to that of human serum with respect to its substrate affinity and specificity and thus designated L-PAF-AH. On the other hand, the primary amino acid sequence of L-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 42 publications
1
15
0
1
Order By: Relevance
“…Previously, we found that Mongolian gerbil has its normal pPAF-AH level similar to that of human, and the patterns of the change of PAF-AH level in serum during the course of severe leptospirosis in gerbil model are similar to that of severe leptospirosis patients, including the levels of elevation [8]. These findings were consistent with the fact that LPS of Leptospira interrogans is much less virulent than that of Escherichia coli , and has little effect on the sepsis caused by leptospirosis [13].…”
Section: Introductionmentioning
confidence: 71%
“…Previously, we found that Mongolian gerbil has its normal pPAF-AH level similar to that of human, and the patterns of the change of PAF-AH level in serum during the course of severe leptospirosis in gerbil model are similar to that of severe leptospirosis patients, including the levels of elevation [8]. These findings were consistent with the fact that LPS of Leptospira interrogans is much less virulent than that of Escherichia coli , and has little effect on the sepsis caused by leptospirosis [13].…”
Section: Introductionmentioning
confidence: 71%
“…The PAF acetylhydrolase activity of SsE appears at least to be as potent as the human plasma PAF acetylhydrolase. PAF acetylhydrolase activity has also been detected in bacteria and yeast [36], [37], [38]. While the yeast PAF acetylhydrolase enhances the viability of yeast under oxidative stress, the function of L. interrogans PAF acetylhydrolase and Est13 is not known.…”
Section: Discussionmentioning
confidence: 99%
“…An intracellular yeast group VII PAF-AH enhances the viability of yeast under oxidative stress (29). The spirochete Leptospira interrogans produces a PAF-AH (30). An apparently intracellular esterase Est13 from an earthworm gut-associated microorganism inhibits PAF-induced platelet aggregation (31).…”
Section: M28mentioning
confidence: 99%